– The position of orientalists from Zionism – Chomsky is a model - ALBALOCHI, ABDULRAHIM SAHRAB (Journal of Islamic Sciences, 2019)
Zionism: an extreme racist political movement aimed at establishing a state for the Jews in Palestine through which the entire world rules and controls it. It preaches revenge against non- Jews. This movement has resonated with Muslims, even some orientalists, including Noam Chomsky. He expressed his opinion on this movement through his book: Illusions of the Middle East, taking the method of inductive and documentary and analytical and analytical, and reached several results, notably: the position of the Muslim position of justice in the ruling on the violator does not release judgments arbitrarily, but be fair, the opinion of orientalists on Zionism between a supporter Exhibitions, and all his justification and opinion. Noam Chomsky in his book: Illusions of the Middle East is contrary to this movement explicitly and prejudice.